Characterization of Post–exertional Malaise in Patients With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Stussman, Barbara; Williams, Ashley; Snow, Joseph; Gavin, Angelique; Scott, Remle; Nath, Avindra; Walitt, Brian (Frontiers in Neurology, 2020)
Background: Myalgic encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is characterized by persistent and disabling fatigue, exercise intolerance, cognitive difficulty, and musculoskeletal/joint pain. Post-exertional malaise is a worsening of these symptoms after a physical or mental exertion and is considered a central feature of the illness. Scant observations in the available literature provide qualitative assessments of post-exertional malaise in patients with ME/CFS. To enhance our understanding, a series of outpatient focus groups were convened. Methods: Nine focus groups totaling 43 self-reported ME/CFS patients were held between November 2016 and August 2019. Focus groups queried post-exertional malaise in daily life and participants’ retrospective memory of post-exertional malaise that followed an exercise provocation with a cardiopulmonary exercise test. Thematic analysis was used to systematically code and categorize the data for meaningful patterns to emerge. A qualitative software package was used to assist with data coding. Results: A wide range of symptoms were attributed to exertion both in daily lives and following cardiopulmonary exercise testing. While three major themes emerged (exhaustion, cognitive difficulties, and neuromuscular complaints), participants’ descriptions were notable for their unique individual variations. Of 18 participants who responded to questions centered around symptoms following a cardiopulmonary exercise test, 17 reported that symptoms started within 24 hours and peaked in severity within 72 hours following the cardiopulmonary exercise test. Conclusion: The experience of post-exertional malaise in ME/CFS varies greatly between individuals. Quantitative questionnaires using fixed questions may misclassify or fail to capture the entire experience of post-exertional malaise. A mixed methods approach appears necessary to evaluate ME/CFS patients for symptom outcomes and the development of management strategies.